IMPROVE THE PERFORMANCE OF THE THERMAL ENGINE USING ELECTRO AFFECTING - Терещенко, Ю. М.; Морозов, В. І.; Морозова, І. В. (Science-based technologies, 2016)
Some aspects of the method of application electrophysical impact on fuel in order to improve the operational performance of heat engines.